AB0667 ACHILLES PAIN PERSISTENCE IN PATIENTS AFFECTED BY SPONDYLOARTHRITIS: ULTRASONOGRAPHIC AND BIOMECHANICAL STUDY. (2nd June 2020) - Batticciotto, A.; Olivieri, S.; Talotta, R.; Cappelli, A.; Preda, A.; Sarzi-Puttini, P.
Abstract : Background: Enthesis anatomy and biomechanics have a key role in Spondyloarthritis (SpA) pathogenesis (1) but few data are available about the influence of structural and biomechanical changes of Achilles tendon (AT) on persisting pain in longstanding SpA patients. Objectives: To correlate AT pain in longstanding SpA patients with ultrasonographic detectable disorders and biomechanical abnormalities. Methods: We performed a monocentric cross-sectional analysis including 35 consecutive patients affected by SpA (13 with Psoriatic Arthritis, 9 with Enteropathic SpA, 6 with Ankylosing Spondylitis and 7 with Undifferentiated SpA) under treatment with anti- TNF agents. A rheumatologic clinical and clinimetric evaluation (AT VAS pain, BASDAI, BASFI, HAQ), an ultrasound study of AT according to the Madrid Sonographic Enthesis Index (MASEI) score and a podiatrist biomechanical evaluation [Foot posture index (FPI), degree of ankle dorsiflexion with the knee extended and flexed] were performed. Results: Study population (13 F; 22 M; mean age 54.9 ±13.9 years; mean disease duration 9.5 ± 5.0 years; mean BMI 25.8 ±4.4) showed a mean AT VAS pain of 3.4 ± 2.2, a mean HAQ of 0.6 ± 0.6, a mean BASDAI of 3.3 ±2.1 and a mean BASFI of 2.2 ±1.9. At the ultrasonographic evaluation 47% (33/70) of the AT entheses analysed presented a dishomogeneous echostructure, 31% (22/70) structural thickness, 53% (37/70) calcifications, 10% (7/70) erosions, 44% (31/70) a retrocalcanear bursitis. A power Doppler positivity was found only in 0.07% (5/70) of the AT. At the biomechanical evaluation 50% (35/70) of the feet showed a FPI score between 0 and + 5 (neutral foot), 46% (32/70) a FPI score between +6 and +9 (slight foot pronation) and 6% (4/70) a FPI score between -1 and -4 (slight foot supination). The mean degree of ankle dorsiflexion with extended knee was 8.4 ± 3.9 with the 61% (43/70) of the patients with a maximum dorsiflexion < 10° of whom 46% (20/43) do not recover after the knee flexion. We found a between the mean degree of left ankle dorsiflexion with extended/flexed knee both with ultrasound-revealed left AT enthesis calcifications (p=0.014/0.037) and with left AT enthesis thickness (p=0.049/0.035), and a significant association between the mean degree of right ankle dorsiflexion and extended/flexed knee and ultrasound-revealed right AT calcifications (p=0.008/0.012). Moreover, we noticed an inverse correlation between the mean overall degree of ankle dorsiflexion with extended/flexed knee and the BASFI values (p=0.007/0.004). AT VAS pain was statistically related with Achilles PDUS signal persistence (p=0.048) but not with US signs of chronic entesopathy or biomechanical alterations [calcification (p=0.39), erosions (p=0.74)]. The limits of the study were the low number of patients recruited and the lack of a control group. Conclusion: In this monocentric study on a cohort of SpA patients, we demonstrated a statistically significant correlation between ankle–subtalar joint complex biomechanics alterations, ultrasonographic signs of chronic enthesopathy and clinimetric index of functional disability. Residual Achilles pain seems to be related to US signs of active enthesitis. References: [1]The enthesis organ concept and its relevance to the spondyloarthropathies. Benjamin, M and McGonagle, D. s.l.: Adv Exp Med Biol, 2009, Vol. 649. [2]The Synovio-entheseal Complex and Its Role in Tendon and Capsular Associated Inflammation. McGonagle, E D, Aydin, SZ and Tan, AL. 0, s.l.: J Rheumatol Suppl, 2012, Vol. 89 Disclosure of Interests: None declared